Nursing Care In Ny. W With Complaints Of Abdomial Pain At Kardinah Regional General Hospital, Tegal City - Widia Pitriyani; Suci Khasanah (Asosiasi Riset Ilmu Kesehatan Indonesia, 2024)
Abnormal pain is a general term encompassing various health complaints affecting the area between the chest and pelvis (including the abdominal wall and internal organs), with varying intensity, duration, and pain points. The research aims to identify the application of nursing care for acute pain by providing warm compresses to a patient with the initials Ny.W, who experienced abnormal pain in the Lavender ward at Kardinah Regional Hospital, Tegal City. This study applied a descriptive design. Data were collected through several stages, including anamnesis (gathering of medical history), direct observation, physical assessment, and documentation. The research findings indicated that the patient's issue was resolved on the third day, marked by a reduction in pain intensity. Overall, the nursing problem was managed within three days through the intervention of warm compresses as a nursing action.